On the Role of Additional [4Fe-4S] Clusters with a Free Coordination Site in Radical-SAM Enzymes - Mulliez, Etienne; Duarte, Victor; Arragain, Simon; Fontecave, Marc; Atta, Mohamed (Frontiers in Chemistry, 2017)
The canonical CysXXXCysXXCys motif is the hallmark of the Radical-SAM superfamily. This motif is responsible for the ligation of a [4Fe-4S] cluster containing a free coordination site available for SAM binding. The five enzymes MoaA, TYW1, MiaB, RimO and LipA contain in addition a second [4Fe-4S] cluster itself bound to three other cysteines and thus also displaying a potentially free coordination site. This review article summarizes recent important achievements obtained on these five enzymes with the main focus to delineate the role of this additional [4Fe-4S] cluster in catalysis.